Sexually dimorphic effects of catechol-O-methyltransferase (COMT) inhibition on dopamine metabolism in multiple brain regions - Laatikainen, L; Sharp, T; Harrison, P; Tunbridge, E (Public Library of Science, 2013)
The catechol-O-methyltransferase (COMT) enzyme metabolises catecholamines. COMT inhibitors are licensed for the adjunctive treatment of Parkinson's disease and are attractive therapeutic candidates for other neuropsychiatric conditions. COMT regulates dopamine levels in the prefrontal cortex (PFC) but plays a lesser role in the striatum. However, its significance in other brain regions is largely unknown, despite its links with a broad range of behavioural phenotypes hinting at more widespread effects. Here, we investigated the effect of acute systemic administration of the brain-penetrant COMT inhibitor tolcapone on tissue levels of dopamine, noradrenaline, and the dopamine metabolites 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA). We examined PFC, striatum, hippocampus and cerebellum in the rat. We studied both males and females, given sexual dimorphisms in several aspects of COMT's function. Compared with vehicle, tolcapone significantly increased dopamine levels in the ventral hippocampus, but did not affect dopamine in other regions, nor noradrenaline in any region investigated. Tolcapone increased DOPAC and/or decreased HVA in all brain regions studied. Notably, several of the changes in DOPAC and HVA, particularly those in PFC, were more prominent in females than males. These data demonstrate that COMT alters ventral hippocampal dopamine levels, as well as regulating dopamine metabolism in all brain regions studied. They demonstrate that COMT is of significance beyond the PFC, consistent with its links with a broad range of behavioural phenotypes. Furthermore, they suggest that the impact of tolcapone may be greater in females than males, a finding which may be of clinical significance in terms of the efficacy and dosing of COMT inhibitors.